Multi-scale response of sustainable self-compacting concrete (SCC) to carbonation and chloride penetration - Mohammed, Mahmoud khashaa (2015)
The work described in this thesis has been performed in order to gain further understanding of the relationship between the microstructural characteristics of some common types of medium to high strength sustainable Self- Compacting Concretes (SCCs) (especially the internal pore structure, the interfacial transition zone (ITZ), and chemical composition) and the carbon dioxide and chloride diffusivities. This was done by evaluating the diffusion coefficients with the aid of some selected and modified accelerated tests at the macro scale.